Pengaruh Kebijakan Hutang dan Transfer Pricing terhadap Tax Avoidance dengan Kualitas Audit sebagai Variabel Moderasi - Pinkan Novtalia Zaskia; Indah Hapsari (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to examine the effect of debt policy and transfer pricing on tax avoidance, with audit quality as a moderating variable. The object of this study is non-banking companies included in the LQ45 index listed on the Indonesia Stock Exchange during 2021-2024, with a total sample of 117 firm-year observations. The data were analyzed using multiple linear regression and subgroup analysis (and chow test), by comparing the regression results between companies audited by Big Four and non-Big Four audit firms. The results indicate that debt policy has a positive and significant effect on tax avoidance, while transfer pricing does not have a significant effect on tax avoidance. Audit quality is proven to moderate the relationship between debt policy and tax avoidance by weakening the effect. However, audit quality does not moderate the relationship between transfer pricing and tax avoidance. These findings suggest that corporate financing decisions through debt remain an important mechanism in tax planning practices, while audit quality plays a crucial role as an external monitoring mechanism in limiting aggressive tax avoidance behavior.